The heart of the prosperity gospel : self or the savior? - Lioy, Dan (Conspectus : The Journal of the South African Theological Seminary, 2007)
This essay explores whether self or the Savior is at the heart of the prosperity gospel. An analysis and critique of its dogma indicates that it is predominantly anthropocentric, rather than Christocentric. This ego-focused outlook is likewise present in the health-and-wealth movement. One discovers that preachers of success are touting a religion of self in which people are the measure of all things. A detailed discussion of Ephesians 1 : 3-23 provides a needed biblical response. One learns that the Son, not self, is at the heart of the Father's plan of redemption. Also, it is in Christ alone that believers find forgiveness, hope, and wisdom. Only He is the meta-narrative of life, whether temporal or eternal in nature. Indeed, He is the sole reason for the existence of the church and the one who enables believers to complete their God-given work.
free